Measurement Advances and Challenges in Competency Assessment in Higher Education. Issue 3 (August 2016) - Zlatkin‐Troitschanskaia, Olga; Pant, Hans Anand
Abstract : Domain‐specific and generic competencies have become target outcomes of students' learning in higher education, and competency assessment plays an increasingly important role in higher education on an international scale. Recent reviews of the literature show that there is still a substantial lack of research on assessment practices in higher education, especially on measurement models and valid instruments for competency assessment. This special issue provides an overview of current international research and innovative developments in this research area, covering a broad range of assessment perspectives, addressing prevalent shortcomings of educational assessment practices, and presenting novel conceptual and methodological approaches from various fields, including cognitive psychology, educational testing methodology, and psychometrics. This special issue is meant to provide new incentives for enhancing competency assessment, and thus, improving instructional practice and student learning outcomes.